Role of Intravascular Ultrasound in Guiding Complex Percutaneous Coronary Interventions - Brandon Quintana (Radcliffe Medical Media, 2020)
Complex percutaneous coronary interventions (PCIs) are increasing in frequency due to the rapid advances in interventional cardiology. This has had a favorable impact on patients with extensive coronary artery disease and multiple comorbidities with regard to symptomatic relief and mortality. With this increase, cardiologists must develop a standardized way to approach complex PCI in an era in which angiographic guidance alone yields suboptimal results. Intravascular ultrasound (IVUS) has been shown to improve outcomes with better preprocedural planning, improved stent placement, and larger stent diameters. Considering the supportive data, the use of IVUS is crucial in all cases of complex PCI.